Repairing Old and Damaged Cocoa Plants Through Rehabilitation Without the Felling of Trees - Palad, Marliana S.; Aminah, Aminah; Nasaruddin, Nasaruddin; Suryani, Ida; Mutiara, Ravika (AGRIVITA Journal of Agricultural Science, 2025)
This study aims to evaluate the effectiveness of Trichoderma asperellum and Azotobacter chroococcum in providing nutrients and nutrient uptake after treatment inarching grafting on cocoa trees' rehabilitation efforts. The Split Plot Design, with two factors, namely the application of T. asperellum and A. chroococcum were repeated three times and continued using ANOVA and Tukey HSD at a 5%. Rehabilitation of cocoa plants that are relatively old age can be done without the need to cut down a cocoa tree, by way of modification Inarching grafting with environmentally friendly farming systems, so that farmers do not need a long time to produce cocoa beans. This research concluded that the inarching grafting method can be used to rehabilitate cocoa plants of relatively old ages and damage, with applications, T. asperellum (4 g/l) and A. chroococcum (4 × 108 CFU/ml) the dose of 40 ml per plant with a frequency of twice application to each plant. This treatment is the best interaction that can reduce the number of young fruits falling (74.15%), boost the number of flowers (264.71%), the number of young fruits formed (271.65%), and the number of surviving fruits (117%) and production.